Impact of tissue macrophage proliferation on peripheral and systemic insulin resistance in obese mice with diabetes. Issue 1 (21st October 2020) - Morita, Yutaro; Senokuchi, Takafumi; Yamada, Sarie; Wada, Toshiaki; Furusho, Tatsuya; Matsumura, Takeshi; Ishii, Norio; Nishida, Saiko; Nishida, Syuhei; Motoshima, Hiroyuki; Komohara, Yoshihiro; Yamagata, Kazuya; et al.
Abstract : Introduction: Obesity-related insulin resistance is a widely accepted pathophysiological feature in type 2 diabetes. Systemic metabolism and immunity are closely related, and obesity represents impaired immune function that predisposes individuals to systemic chronic inflammation. Increased macrophage infiltration and activation in peripheral insulin target tissues in obese subjects are strongly related to insulin resistance. Using a macrophage-specific proliferation inhibition mouse model (mac-p27Tg), we previously reported that suppressed plaque inflammation reduced atherosclerosis and improved plaque stabilization. However, the direct evidence that proliferating macrophages are responsible for inducing insulin resistance was not provided. Research design and methods: The mac-p27Tg mice were fed a high-fat diet, and glucose metabolism, histological changes, macrophage polarization, and tissue functions were investigated to reveal the significance of tissue macrophage proliferation in insulin resistance and obesity. Results: The mac-p27Tg mice showed improved glucose tolerance and insulin sensitivity, along with a decrease in the number and ratio of inflammatory macrophages. Obesity-induced inflammation and oxidative stress was attenuated in white adipose tissue, liver, and gastrocnemius. Histological changes related to insulin resistance, such as liver steatosis/fibrosis, adipocyte enlargement, and skeletal muscle fiber transformation to fast type, were ameliorated in mac-p27Tg mice. Serum tumor necrosis factor alpha and free fatty acid were decreased, which might partially impact improved insulin sensitivity and histological changes. Conclusions: Macrophage proliferation in adipose tissue, liver, and skeletal muscle was involved in promoting the development of systemic insulin resistance. Controlling the number of tissue macrophages by inhibiting macrophage proliferation could be a therapeutic target for insulin resistance and type 2 diabetes.